Legal Protection for Investment in Indonesia - Yusna Wulan Sari Tanung (IHSA Institute, 2021)
As a sovereign and prosperous legal state, Indonesia is very concerned about all forms that are directly related to its people, this is the government's concern for the development and growth of the national economy, which in fact is still far from being expected. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that national development efforts through investment and foreign investment activities will actually have a positive impact on the growth and development of the national economy, in addition to holding these activities able to develop various sectors in the government. Indonesia, it is hoped that through foreign investment, the national economy can develop rapidly, because the responsibility for national growth is a shared responsibility and must be carried out with laws and values in accordance with the constitution and Pancasila as the legal basis of the Indonesian nation.